2018
DOI: 10.3892/ol.2018.8745
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary tumor‑transforming 1 expression in laryngeal cancer and its association with prognosis

Abstract: The purpose of the present study was to investigate the association between the expression of pituitary tumor-transforming 1 (PTTG1) and the expression of matrix metalloproteinase (MMP)-2 and MMP-9 in laryngeal carcinoma tissues, and to elucidate the association between PTTG1 expression and the prognosis of patients with laryngeal cancer. Immunohistochemical staining was used to detect PTTG1 expression in laryngeal cancer and normal tumor-adjacent laryngeal tissues. Western blotting was used to determine the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The percentage of stained cells was calculated as: 0, <5% stained; 1+, 5% to 25% stained; 2+, 26% to 50% stained; 3+, 51% to 75% stained; 4+, 76% to 100% stained. As shown in previously published studies, the product of the two staining variable scores represented the Tra2β score for each sample. A score of ≥6 was considered high expression, whereas a score < 6 was considered low expression.…”
Section: Methodsmentioning
confidence: 96%
See 1 more Smart Citation
“…The percentage of stained cells was calculated as: 0, <5% stained; 1+, 5% to 25% stained; 2+, 26% to 50% stained; 3+, 51% to 75% stained; 4+, 76% to 100% stained. As shown in previously published studies, the product of the two staining variable scores represented the Tra2β score for each sample. A score of ≥6 was considered high expression, whereas a score < 6 was considered low expression.…”
Section: Methodsmentioning
confidence: 96%
“…Accordingly, the present findings suggested that abnormal expression of Tra2β is associated with LSCC progression, and Tra2β may play an important role in diagnosis and served as a potential biomarker, as other studies previously reported. [13][14][15][16][17][18][19][20][21][22][23][24][25]…”
Section: Tra2β Is Upregulated In Lscc Tissues and Significantly Assocmentioning
confidence: 99%
“…At last, A total of 25 articles with 26 studies were selected for this meta-analysis. [2,9,[17][18][19][21][22][23][25][26][27][28][38][39][40][41][42][43][44][45][46][47][48][49][50] A flowchart of the study search and selection process is depicted in Figure 1.…”
Section: Literature Search and Selectionmentioning
confidence: 99%
“…Nevertheless, these studies have yielded conflicting results regarding the prognostic significance of securin in human cancers. Most studies indicate that high securin expression is closely correlated with poorer overall survival (OS) and even acts as an independent prognostic biomarker in patients with malignant tumors, such as esophageal cancer, [ 2 ] HCC, [ 17 , 18 ] endometrial cancer, [ 19 , 20 ] glioma, [ 21 ] gastric cancer, [ 22 ] laryngeal cancer, [ 23 , 24 ] lung cancer, [ 9 , 25 ] colorectal cancer, [ 26 ] renal cell cancer, [ 27 ] osteosarcoma, and bladder cancer. [ 28 ] Conversely, one individual study has shown that the securin expression level is not related to survival outcome in cancer patients.…”
Section: Introductionmentioning
confidence: 99%